Finger Exercises for Oscillators: István Anhalt on Electronic Music - Rogalsky, Matt (Circuit, 2009)
AbstractIn conversation with Matt Rogalsky, composer István Anhalt discusses his association with Hugh Le Caine and the National Research Council laboratories in the 1950s, the founding of the electronic music studio at McGill, and his early experiences learning tape music and analog and digital synthesis techniques. The composer describes his early electronic works, the use of electroacoustic elements in his later music, and the importance of electroacoustic music in music education.